2021
DOI: 10.5545/sv-jme.2021.7246
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Laser Parameters and Dimple Geometry Using PCA-Coupled GRG

Abstract: Stainless steel (SS316L) is applied in numerous fields due to its intrinsic properties. In this study, micro-dimples were fabricated on SS316L. The effects of laser process parameters, such as frequency, average power, and pulse duration, on the average dimple diameter, dimple distance, and dimple depth were studied using an L9 orthogonal array. The analysis of variance (ANOVA) and multi-objective optimization technique, principal-component-analysis-coupled grey relational grade (GRG), was used to optimize las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
(14 reference statements)
1
10
0
Order By: Relevance
“…High µ occurred, owing to destruction of these tribo-layers. These findings were in agreement with literature data [22] to [24].…”
Section: Effect Of Load On µ and A Wsupporting
confidence: 94%
See 2 more Smart Citations
“…High µ occurred, owing to destruction of these tribo-layers. These findings were in agreement with literature data [22] to [24].…”
Section: Effect Of Load On µ and A Wsupporting
confidence: 94%
“…For multi-objective optimization, GRA has been developed exploiting the Taguchi design to estimate the degree of correlation between test trials (series) via grey relational grade (GRG). To reduce data inconsistency, the data is normalized to a comparable range between 0 and1 [22]. Different objective functions exist, such as larger is better and smaller is better.…”
Section: Abrasive Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Many data preprocessing techniques can be utilized in Taguchi-Deng method, depending upon the features of the actual sequence. Generally, series is normalized between 0 and 1 20 . For this study, the target value is “the smaller the better”.…”
Section: Methodsmentioning
confidence: 99%
“…ANOVA showed that speed significantly affect the wear property of the co-continuous composite. Savaran and Thanigaivelan 20 optimized dimple geometry and laser parameter using principal component analysis (PCA) coupled GRA. ANOVA showed that average power contributed most while depth contributed less to performance measures.…”
Section: Introductionmentioning
confidence: 99%